Benefits of Early Orthodontics Intervention in Children: A Review - Debashreeta Nanda (Institute of Medico-legal Publications Pvt Ltd, 2020)
When it comes to your children orthodontic treatment then a diamond seems less precious than time. Thereis an optimal time span to begin your child’s early intervention treatment. Mixed dentition is a periodof development following the eruption of permanent 1st molar and incisors. During this period, phase-1treatment is done earlier and often a mixed dentition treatment is meant to concentrate on modification ofskeletal system rather than dental system. At little smile’s our goal is to provide both timely detection ofproblems and greater opportunity for more effective treatment to benefit your child/children. The dentistmust understand the growth and development patterns before planning a treatment, as jaw growth is theprimary factor in orthodontic treatment. Though comprehensive treatment may be required at a later date,the need for early intervention cannot be denied.